Biological activity of Myrtaceae plant essential oils and their major components against Drosophila suzukii (Diptera: Drosophilidae). Issue 2 (11th November 2016) - Jang, Miyeon; Kim, Junheon; Yoon, Kyungjae Andrew; Lee, Si Hyeock; Park, Chung Gyoo
Abstract: BACKGROUND: The spotted‐wing drosophila (SWD), Drosophila suzukii (Matsumura), is a globally invasive and serious pest of numerous soft‐skinned fruit crops. Assessments were made of fumigant and contact toxicities of 12 Myrtaceae plant essential oils (EOs) and their components. For determining the mode of action of major components of active EOs, their activities against acetylcholinesterase (AChE) and Glutathione S ‐transferase (GST) were also assessed. RESULTS: Strong fumigant and contact toxicities were observed from EOs of Eucalyptus citriodora and Melaleuca teretifolia . The main components of E . citriodora were citronellal and isopulegol, whereas those of M. teretifolia were neral and geranial. Geranial showed the strongest fumigant activity, followed by citronellal or neral, M. teretifolia EO, isopulegol and E . citriodora EO. In contact toxicity assays, geranial also exhibited the strongest insecticidal activity, followed by neral or M. teretifolia EO, citronellol, citronellal, isopulegol and E . citriodora EO. Among the major components, all compounds showed low AChE inhibitory activity, while neral and geranial showed GST inhibitory activity against SWD. CONCLUSION: Myrtaceae plant EOs and their components have an excellent potential for being used in the control of SWD adults and could be useful in the development of more effective natural compounds as alternatives to synthetic pesticides. © 2016 Society of Chemical Industry